ANALISIS CUSTOMER ORIENTED TERHADAP KEPUASAN PELANGGAN DEL MANGGO MAKASSAR - Verawaty; Imam Islah; Abigail Jaya Pakkung (LP2M IBK Nitro, 2021)
The purpose of this study was to analyze the effect of customer oriented, namely company commitment, fulfillment of needs and response to complains on customer satisfaction at Del Mango Macassar. The results of this study indicate that customer oriented from company commitment, fulfillment of needs and response to complaints at Del Mango Macassar affects customer satisfaction.